2010
DOI: 10.1111/j.1460-9568.2010.07247.x
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A1 and A2A receptors are not upstream of caffeine’s dopamine D2 receptor‐dependent aversive effects and dopamine‐independent rewarding effects

Abstract: Caffeine is widely consumed throughout the world, yet little is known about the mechanisms underlying its rewarding and aversive properties. We show that pharmacological antagonism of dopamine not only blocks conditioned place aversions to caffeine, but reveals dopamine blockadeinduced conditioned place preferences. These aversions are mediated by the dopamine D 2 receptor since knockout mice showed conditioned place preferences to doses of caffeine that C57Bl/6 mice found aversive. Further, these aversions ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 72 publications
(164 reference statements)
2
15
0
Order By: Relevance
“…We have elicited separately conditioned caffeine reward through low-dose systemic injections and intra-rVTA caffeine, or conditioned caffeine aversions through higher dose systemic injections by performing in vivo administration of caffeine in a place conditioning paradigm. While our study aligns generally with the findings reported previously by us and by others (Brockwell, Eikelboom, & Beninger, 1991;Patkina & Zvartau, 1998;Sturgess et al, 2010), there are several inconsistencies and F I G U R E 6 Intra-rVTA caffeine reward and systemic (10 mg/kg i.p.) caffeine aversion are both DA-dependent, but segregated in the NAc shell and NAc core, respectively.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We have elicited separately conditioned caffeine reward through low-dose systemic injections and intra-rVTA caffeine, or conditioned caffeine aversions through higher dose systemic injections by performing in vivo administration of caffeine in a place conditioning paradigm. While our study aligns generally with the findings reported previously by us and by others (Brockwell, Eikelboom, & Beninger, 1991;Patkina & Zvartau, 1998;Sturgess et al, 2010), there are several inconsistencies and F I G U R E 6 Intra-rVTA caffeine reward and systemic (10 mg/kg i.p.) caffeine aversion are both DA-dependent, but segregated in the NAc shell and NAc core, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…This could be due to unknown compensatory mechanisms arising from transgenic manipulation. Nonetheless, downstream dopaminergic mechanisms were implicated in the aversive response to caffeine, as systemic pharmacological blockade of DA receptors reduced caffeine aversions (Sturgess et al, 2010). As caffeine may not act as an adenosine receptor antagonist to produce these motivational effects and does not bind directly to DA receptors as demonstrated by radioligand competitive binding assays (Watanabe & Uramoto, 1986), caffeine could be acting on an unknown receptor to produce a motivational response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caffeine, a xanthine alkaloid, is naturally found in a lot of different plants worldwide and acts as a central nervous system and metabolic stimulant. The CNS stimulating effects of caffeine have been reported in numerous preclinical studies (Kuzmin et al, 2006;Popoli et al, 1996;Sturgess et al, 2010;Xu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The necessity of this DA system in the rewarding properties of benzodiazepines, barbiturates and caffeine is also questioned [29,31,32]. A rising hypothesis asserts that DA is not requisite for all rewarding effects of opiates, cannabis, cocaine and NIC.…”
Section: Dopamine Independent Mechanisms In the Mesolimbic Systemmentioning
confidence: 99%